Effect of Education for Hypertensive Patients with Correctly Performed Self-Blood Pressure Monitoring (SBPM) - Justyna Dymek; Anna Gołda; Wioletta Polak; Bartosz Lisowski; Agnieszka Skowron (MDPI AG, 2019)
Introduction: The study objective was to assess the impact of pharmacist-led education on the patient’s knowledge and skills on SBPM (self-blood pressure monitoring). Methods: Patient knowledge was assessed using tests and patients’ skills were based on a checklist (20 parameters) completed by the researcher based on the SBPM video records. Patients taking pressure measurements were filmed for 20 days and after 6 months. After the first 10 days, patients were educated about the correct SBPM procedure. Knowledge tests were repeated three times (before/after/6 months after education). Results: All patients’ knowledge and skills in the field of SBPM were improved after education. After the education, patients scored an average of 9 out of 10 points in the knowledge test (increasing an average of five points after education), six months later—an average increase of 7.36 points. Patient skills after training were rated at 17.4 out of 20 points on average (increase by an average of 5.14 points after education), six months later, there was an average of 16.23 points. Conclusions: The study showed an increase in patients' knowledge and skills in the field of SBPM after training.